Rancang Bangun Aplikasi Penjadwalan Ujian Di Institut Bisnis dan Informatika Stikom Surabaya Dengan Menggunakan Algoritma Genetika - Alvian Deffa Kristyanto; A. B. Tjandrarini; Tutut Wurijanto (Jurnal Sistem Informasi Universitas Dinamika, 2018)
Universities have activities that will be able to support education activities which take place. Activities to support the education process is the scheduling activities conducted by the Institute of Business and Medical Informatics Stikom Surabaya one rescheduling process test.The fact that occurred in the preparation of the current test schedule requires the process and a long time. This happens because the application that is currently unable to meet the need and must arrange the schedule with the help of Microsoft Excel. When arrange the schedule the test in a way that is done when the difficulties faced by the arrange the schedule the test to meet the conditions and policies that have been determined. When it is left then the Son need more resources to arrange a trial, and it will be discussed how to solve the problem is in the scheduling using a method that is algorithm genetic algorithm. Genetic algorithms can be used for the needs of the preparation of the schedule that meets the conditions of the terms and the policy that has been determined the results of the study showed that the test scheduling applications can help the Son to provide information on the schedule of the tests in one semester and are able to include the conditions and the existing policy at the Institute of Business and Medical Informatics Stikom Surabaya.